2020
DOI: 10.2147/pgpm.s273125
|View full text |Cite
|
Sign up to set email alerts
|

<p>Genetic Association of Epilepsy and Anti-Epileptic Drugs Treatment in Jordanian Patients</p>

Abstract: The aim of this study was to investigate the possible effects of single-nucleotide polymorphisms (SNPs) within SLC1A1, SLC6A1, FAM131B, GPLD1, F2, GABRG2, GABRA1, and CACNG5 genes on response to anti-epileptic drugs (AEDs) and the genetic predisposition of epilepsy in Jordanian patients. Patients and Methods: A total of 299 healthy individuals and 296 pediatric patients from the Jordanian population were recruited. Blood samples are collected, and genotyping was performed using a custom platform array analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…A significant association of the rs2279020 with epilepsy risk was reported by some research groups (16, 26, 32), whereas no significant association was reported by other research groups (13,17,23,25). The controversial results were also observed in comparison to the rs2279020 with AED resistance (16,17,24,25). For example, some authors reported that the rs2279020 was a risk factor for affecting treatment efficacy (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A significant association of the rs2279020 with epilepsy risk was reported by some research groups (16, 26, 32), whereas no significant association was reported by other research groups (13,17,23,25). The controversial results were also observed in comparison to the rs2279020 with AED resistance (16,17,24,25). For example, some authors reported that the rs2279020 was a risk factor for affecting treatment efficacy (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, an SNP located in intron 10 of GABRA1 (rs2279020) was reported to be potentially functional, with the A→ G shift changing the shape of the protein that led to alternative splicing (32). A significant association of the rs2279020 with epilepsy risk was reported by some research groups (16, 26, 32), whereas no significant association was reported by other research groups (13,17,23,25). The controversial results were also observed in comparison to the rs2279020 with AED resistance (16,17,24,25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacogenetics investigates the association between genetic markers and the pharmacokinetics and pharmacodynamics of the drug and aims at predicting the individual therapy response based on these associations ( Valdes and Yin, 2016 ). In recent times, advances have been made in neuropsychiatry regarding the understanding of the role of genetic polymorphisms in therapy response to treatment approaches as in major depressive disorder ( Shalimova et al, 2021 ), schizophrenia ( Jovanović et al, 2010 ), or epilepsy ( Al-Eitan et al, 2020 ). The role of pharmacogenetics for therapy success with compounds used for the treatment of headache disorders is not as largely investigated, and pharmacogenetic information is hitherto practically not used to predict efficacy or adverse effects in clinical practice in this field ( Christensen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%